Theoretical Research Progress in High-Velocity/Hypervelocity Impact on Semi-Infinite Targets - Yunhou Sun; Cuncheng Shi; Zheng Liu; Desheng Wen (Shock and Vibration)
With the hypervelocity kinetic weapon and hypersonic cruise missiles research projects being carried out, the damage mechanism for high-velocity/hypervelocity projectile impact on semi-infinite targets has become the research keystone in impact dynamics. Theoretical research progress in high-velocity/hypervelocity impact on semi-infinite targets was reviewed in this paper. The evaluation methods for critical velocity of high-velocity and hypervelocity impact were summarized. The crater shape, crater scaling laws and empirical formulae, and simplified analysis models of crater parameters for spherical projectiles impact on semi-infinite targets were reviewed, so were the long rod penetration state differentiation, penetration depth calculation models for the semifluid, and deformed long rod projectiles. Finally, some research proposals were given for further study.